PENGARUH HARGA DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE (STUDI KASUS PADA HARAPAN MAULINA HIJAB JOMBANG) - Jayanti, Ratna Dwi (STIE PGRI Dewantara Jombang, 2015)
AbstractIn digital era now, the use of internet in the business has entered all lines of business included in the marketing of goods or services. Online sales or which is known as E-commerce, also used by Maulina Hijab Jombang. This research aims to analyze deeper the Influence of Price (X1) and Trust (X2) toward Online purchasing Decision. Type of research is explanatory involving 90 respondents. The analytical methods used were multiple linear regression, t- test and F- test. The result showed that the price factor (X1) is not dominant influenced on online purchase decisions on Maulina Hijab Jombang.Â WhileÂ theÂ â€œtrustâ€Â factorÂ (X2)Â theÂ dominantÂ influenced.Â ThisÂ showsÂ thatÂ consumers Maulina Hijab already believe that the quality of the goods sold is equivalent to the price offered. Keywords: Influence, Price, Confidence, Online Purchase DecisionÂ Â AbstrakDiÂ eraÂ digitalÂ sekarang,Â penggunaanÂ internetÂ dalamÂ bisnisÂ telahÂ memasukiÂ semuaÂ liniÂ bisnis termasuk dalam pemasaran barang atau jasa. penjualan online atau yang dikenal sebagai E- commerce,Â Â jugaÂ Â digunakanÂ Â olehÂ Â MaulinaÂ Â HijabÂ Â Jombang.Â Â PenelitianÂ iniÂ Â bertujuanÂ Â untuk menganalisis lebih dalam Pengaruh Harga (X1) dan Trust (X2) terhadap Keputusan pembelian online.Â JenisÂ penelitianÂ adalahÂ explanatoryÂ melibatkanÂ 90Â responden.Â metodeÂ analisisÂ yang digunakan adalah regresi linier berganda, uji t dan uji F. Hasil penelitian menunjukkan bahwa faktor harga (X1) tidak dominan dipengaruhi terhadap keputusan pembelian online di Maulina Hijab Jombang. Sementara